2023
DOI: 10.1186/s12886-023-02798-4
|View full text |Cite
|
Sign up to set email alerts
|

Simple surgical punctal occlusion with high frequency radiowave electrosurgery

Abstract: Background To introduce and evaluate the efficacy of a simple punctal occlusion technique for dry eye patients. Methods Medical records of 79 eyes from 40 patients refractory to common dry eye conservative treatment who underwent multiple high-frequency radio-wave electro-punctal occlusion were retrospectively reviewed. Pre- and post-procedural ocular surface indices (Schirmer test, tear break-up time (TBUT), and corneal staining grade (Oxford sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The conventional methods for punctal occlusion are thermal Cauterization, Radiofrequency Electrosurgery, Combined Canalicular Cauterization and Punctal Suturing, Punctal Plugs and Punctal Occlusion with Amniotic Membrane [8,[23][24][25][26]. In all fields of medicine, the preferred initial treatment option is typically the least invasive approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional methods for punctal occlusion are thermal Cauterization, Radiofrequency Electrosurgery, Combined Canalicular Cauterization and Punctal Suturing, Punctal Plugs and Punctal Occlusion with Amniotic Membrane [8,[23][24][25][26]. In all fields of medicine, the preferred initial treatment option is typically the least invasive approach.…”
Section: Resultsmentioning
confidence: 99%
“…They claimed that, in spite of effective reported results in these articles for punctal plugs, they unmask the inconclusiveness of this DED treatment [8]. Woo Park et al reported that high-frequency radio-wave electro-punctal occlusion on 79 eyes at Samsung Hospital is a promising treatment for aqueous-deficient dry eye disease (DED) [23].…”
Section: Resultsmentioning
confidence: 99%
“…The participants were asked to open their eyes wide and look straight, and a single ophthalmologist (KK) measured the time taken for a black spot or line to appear on the cornea. Interval between last blink to the first sign of tear film rupture was recorded as TBUT [ 45 , 46 ]. While measuring TBUT, the CFS score (0–9) was also evaluated [ 47 ].…”
Section: Methodsmentioning
confidence: 99%